13 The Ablation Effectiveness Quotient: A Novel Marker to Predict the Success of Atrial Fibrillation Ablation. (31st May 2014) - Wynn, Gareth; Das, Moloy; Bonnett, Laura; Hall, Mark; Snowdon, Richard; Waktare, Johan; Modi, Simon; Todd, Derick; Gupta, Dhiraj
Abstract : Background: Inability to predict clinical success on follow up in spite of successful Pulmonary vein isolation (PVI) remains the Achilles' heel of AF Ablation (AFA). When patients with arrhythmia recurrence (ARec) return to the catheter laboratory they invariably have recovery of radiofrequency (RF) ablation lesion(s) initially considered complete at the original procedure. Hypothesis: High Sensitivity cardiac Troponin T (HScTnT) is a highly specific marker of acute myocardial injury. We postulated that the ratio between post-AFA serum HScTnT levels and the duration of RF ablation would provide a simple measure of ablation effectiveness. We termed this ratio the Ablation Effectiveness Quotient (AEQ) and hypothesised that a high AEQ would correlate directly with clinical success. Methods: We prospectively measured serum HScTnT levels in 60 patients 12–24h after AFA and calculated the AEQ for each patient. Patients were followed up for 6 months with ECGs and Holter monitors. ARec was defined as documented atrial arrhythmia lasting >30 sec. Results: Of 60 patients, 41 (68%) were male and 22 (37%) had paroxysmal AF (PAF). The mean age was 62.2+/- 10.7 years. All 240 pulmonary veins were successfully isolated at the index procedure. Over 6 months' follow up 22 (37%) patients had documented ARec (Group A) and 38 (63%) did not (Group B). On their own, neither RF time (Group A 3470 secs, Group B 3133 secs, p = 0.32) nor mean HScTnT levels (Group A 1172 ng/L, Group B 1384 ng/L, p = 0.24) differed between the groups. Comorbid conditions and left atrial size were likewise not statistically different. However, mean AEQ was significantly lower in Group A (0.34 ± 0.14 ngL -1 s -1 ) than Group B (0.46 ± 0.18 ngL -1 s -1 ), p < 0.01. In patients with PAF, an AEQ of >0.4 ngL -1 s -1 had a specificity of 100% and sensitivity of 91% in predicting freedom from ARec. Discussion: Acute procedural success in achieving PVI does not reliably predict freedom from ARec, probably because of development of peri-lesion oedema that mimics tissue necrosis. Achieving transmurality with the first application of energy, as assessed indirectly with AEQ, would be expected to lead to a low risk of AF recurrence. We have found a strong correlation of AEQ with clinical outcome following AFA. The fact that post-AFA HScTnT levels were not different between patients with and without recurrence suggests that mere extent of atrial myocardial necrosis does not predict AFA success. For patients with PAFan AEQ >0.4 appears to identify patients at very low risk of ARec. Conclusion: The AEQ is a simple, novel way of assessing lesion quality after AFA.A high AEQ appears to correlate well with freedom from ARec in the medium term, particularly in patients with PAF, and may provide new insight into the mechanisms behind delivery of effective ablation lesions. If confirmed in further studies, AEQ may become a valuable tool to guide follow up and advise patients about their chance of ARec after AFA.